Short-term assessment of the sediment deposition rate and water conditions during a rainy season on La Azufrada coral reef, Gorgona Island, Colombia - Lozano-Cortés, Diego F; Giraldo, Alan; Izquierdo, Vanessa (Revista de Biología Tropical, 2014)
One of the major stresses on corals is the settlement of suspended sediment on their surfaces. This leads to the blocking of light, the covering of the coral mucus surface and an increased risk of disease. For this reason sediment deposition on a reef is considered a highly important variable in coral reef studies. With the use of sediment traps and oceanographic sensors, the sediment deposition rate and water conditions during a rainy season (April-May 2009) on a Tropical Eastern Pacific coral reef (La Azufrada) at Gorgona Island in Colombia were investigated. To quantify sediment deposition, sediment traps were established in nine stations along the coral reef (three stations per reef zone: backreef, flat and slope). To minimize disturbance by aquatic organisms in the sediment traps these were filled with hypersaline borax-buffered 10% formaline solution before their deployment; animals found in the filter contents were fixed and stored in a 4% formalin solution, frozen and identified in the laboratory. To determine the water conditions, discrete samples of water from 1 m and 10 m depths were collected using a Niskin bottle. Oceanographic variables (temperature, salinity and dissolved oxygen) as well as turbidity, chlorophyll and nutrient concentration (nitrite, nitrate and phosphorus) were measured in the samples from both depths. Vertical records of temperature and salinity were carried out with a Seabird-19 CTD nearest to La Azufrada and water transparency was measured using a Secchi disk. We found a mean trap collection rate of 23.30±4.34gm-2d-1 and did not detect a significant difference in the trap collection rate among reef zones. The mean temperature and salinity in the coral reef depth zone (0-10m layer) were 26.98±0.19°C and 32.60±0.52, respectively. Fourteen taxonomic groups of invertebrates were detected inside the sediment traps with bivalves and copepods being the most abundant and frequen. The findings presented here constitute the first report of both the potential sediment deposition rates and the water conditions of La Azufrada coral reef. Rev. Biol. Trop. 62 (Suppl. 1): 107-116. Epub 2014 February 01.